Medicinal Properties of Sarpagandha Ghan Vati – A Review - Garg, Naresh Kumar; Doraya, Sumit (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: One of the most well-liked Vedic medicines, sarpagandha (Rauwolfia serpentina), has been utilized since 1000 BC to treat conditions related to high blood pressure. Sarpagandha travels a great distance from British India to Western communities. The majority of the indole alkaloid reserpine, which has been extensively studied over the past 75 years, is responsible for the bioactivities of sarpagandha. Materials and Methods: Material related to Sarpgandha Vati is collected from Ayurvedic text and textbook of modern medicine, respectively. Results: A traditional Ayurvedic remedy known as sarpagandha ghanvati is frequently recommended for insomnia and anxiety. It contains Cannabis sativum, Jatamansi (Nardostachys jatamansi DC. Family: Valerianaceae) roots, Khurasani ajowan (Hyocyamus niger L.; Family: Solanaceae) seeds, and Sarpagandha (roots of R. serpentina L. (Benth.) Ex Kurz; Family: Apocyanaceae). Discussion: The paper aims to review the therapeutic benefits of “Sarpagandha ghan vati” as found in various Ayurvedic texts. Conclusion: In order to get to a potentially helpful conclusion on the safe and efficient usage of sarpagandha in place of reserpine, the article will examine the ideas of the whole herb and its extracts as well as available information in this respect.